Pelatihan Penggunaan Spss Bagi Mahasiswa Doktor Pendidikan Dalam Implikasinya Pada Riset Kuantitatif - Handoko, Handoko; Haenilah, Een Yayah; Siregar, Rabiyatul Adawiyah; Maulina, Dina; Setiyadi, Ag. Bambang (Jurnal Pengabdian Masyarakat Ilmu Pendidikan, 2024)
This community service is motivated by the author's desire to enhance research skills in quantitative studies for Doctoral students in the Education Program at the University of Lampung. The aim of this community service activity is to provide training to students, lecturers, and staff of the Doctoral Education Program (PSDP) at the Faculty of Teacher Training and Education (FKIP) Unila in the use and application of SPSS software in quantitative research. The expected outcome for participants is the ability to independently use and process qualitative research data using SPSS software. The Doctoral Education Program (PSDP) is tasked with preparing students to master various fields of quantitative research, equipping them with the knowledge and skills to strengthen, develop, and produce high-quality research. The ability to conduct research, particularly in quantitative methods, is essential for carrying out daily professional tasks. The results of this community service activity indicate that the SPSS training program for doctoral students in education successfully enhanced the skills and proficiency of PSDP students in using SPSS software for qualitative research topics in the field of education.